PERAN GRUP MUSIK KOREA BTS SEBAGAI BRAND AMBASSADOR TOKOPEDIA: STUDI FENOMENOLOGI KOREAN WAVES DI INDONESIA - Kumaunang, Maria Christy Felinsia (JIKE : Jurnal Ilmu Komunikasi Efek, 2023)
The Korean Wave fever is very influential for the people of Indonesia. The Korean wave has its charm to be used as a reflection of national pride. So that in this era many Indonesian companies want to attract South Korean artists. One of the things that the Korean wave is interested in Indonesia is the pop music industry, also known as K-POP. This study discusses the role of the Korean Musik Group BTS as Tokopedia's Brand Ambassadors. The purpose of this study was to determine the role of BTS as Tokopedia's Brand Ambassador, to find out the level of sales of the Tokopedia company, and why BTS was chosen by Tokopedia. This research method uses a qualitative descriptive analysis method that seeks to describe the citation of facts systematically. This research approach uses a phenomenological approach. The phenomenological approach, according to Polkinghorne (1989) in Creswell (2014: 452), describes the meaning of a life experience of several people about a concept or phenomenon. The data collection process was carried out through online observation and interviews. The results of the study showed that the role of the South Korean male musik group BTS became Tokopedia's Brand Ambassador. To create a brand company, Tokopedia considered that BTS had a purpose and was in harmony with Tokopedia so Tokopedia made them Brand Ambassadors. This is supported by the fact that the majority of Indonesian people Currently, they have switched to using Tokopedia compared to other E-commerce